Modelo matemático e meta-heurística simulated annealing para elaboração de roteiros turísticos com base no tourist trip design problem - Ribeiro, Eric Arantes (2015)
Tourism is an important sector for the world economy and has been growing steadily over recent years. However, a decisive factor for the choice of a tourist destination is the existence of points of interest in the region he wants to visit and, therefore, the information from points of interest in a region should be available. Given the tourist time constraints, it is not possible for him to visit all the attractions and, therefore, it is necessary the creation of tourist routes. Although there are several packages with predefined destinations contemplating most popular locations in recent years has increased the demand for solutions that create custom tours for the needs of each tourist. To meet this new demand Van Oudheusden and Vansteenwegen (2007) proposed the Tourist Trip Design Problem (TTDP) and they suggested that the use of the Orienteering Problem (OP) and its extensions is the best approach to the TTDP. This thesis proposes the development of a mathematical model and a Simulated Annealing (SA) metaheuristic to solve the TTDP. The objective considered is to generate routes that maximize the sum of scores awarded to the attractions based on the degree of interest of the tourist taking into account the time that he has in the locality and the time that each attraction is available to be visited.